Study of the qualitative characteristics of carp surimi powder frozen for different periods - Ahmed A. Hussien (Journal of Kerbala for Agricultural Sciences, 2025)
In this study, the qualitative properties of surimi fish powder produced from storing carp fish in a freezer at -18°C for (0, 2, 4, 6, 8, 10, 12, 14) days were studied, and the chemical composition of the powder was tested, including protein content, oil absorption capacity, density, emulsification and emulsion stability, thiobarbituric acid content, and gelatinous ability. The results showed that increasing the freezing time of fish led to an increase in the values ​​of thiobarbituric acid and an increase in density, and a decrease in other qualitative properties, such as protein solubility, the ability to form powder gel, and the oil absorption capacity. It can be said that long-term storage of carp in freezing led to a decrease in the quality properties of the surimi powder produced.